Is length of time in a stroke unit associated with better outcomes for patients with stroke in Australia? An observational study. Issue 11 (12th November 2018) - Busingye, Doreen; Kilkenny, Monique F; Purvis, Tara; Kim, Joosup; Middleton, Sandy; Campbell, Bruce C V; Cadilhac, Dominique A
Abstract : Objective: Spending at least 90% of hospital admission in a stroke unit (SU) is a recommended indicator of receiving high-quality stroke care. However, whether this makes a difference to patient outcomes is unknown. We aimed to investigate outcomes and factors associated with patients with acute stroke spending at least 90% of their admission in an SU, compared with those having less time in the SU. Design: Observational study using cross-sectional data. Setting: Data from hospitals which participated in the 2015 Stroke Foundation National Audit: Acute Services (Australia) and had an SU. This audit includes an organisational survey and retrospective medical record audit of approximately 40 admissions from each hospital. Participants: Patients admitted to an SU during their acute admission were included. Outcome measures: Hospital-based patient outcomes included length of stay, independence on discharge, severe complications and discharge destination. Patient, organisational and process indicators were included in multilevel logistic modelling to determine factors associated with spending at least 90% of their admission in an SU. Results: Eighty-eight hospitals with an SU audited 2655 cases (median age 76 years, 55% male). Patients who spent at least 90% of their admission in an SU experienced: a length of stay that was 2 days shorter (coefficient −2.77, 95% CI −3.45 to –2.10), fewer severe complications (adjusted OR (aOR) 0.60, 95% CI 0.43 to 0.84) and were less often discharged to residential aged care (aOR 0.59, 95% CI 0.38 to 0.94) than those who had less time in the SU. Patients admitted to an SU within 3 hours of hospital arrival were three times more likely to spend at least 90% of their admission in an SU. Conclusion: Spending at least 90% of time in an SU is a valid measure of stroke care quality as it results in improved patient outcomes. Direct admission to SUs is warranted.